2008
DOI: 10.1038/nm1753
|View full text |Cite
|
Sign up to set email alerts
|

Functional roles for C5a receptors in sepsis

Abstract: The function of the C5a receptors, C5ar (encoded by C5ar) and C5l2 (encoded by Gpr77), especially of C5l2, which was originally termed a 'default receptor', remains a controversial topic. Here we investigated the role of each receptor in the setting of cecal ligation and puncture-induced sepsis by using antibody-induced blockade of C5a receptors and knockout mice. In 'mid-grade' sepsis (30-40% survival), blockade or absence of either C5ar or C5l2 greatly improved survival and attenuated the buildup of proinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
435
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(458 citation statements)
references
References 38 publications
(69 reference statements)
21
435
0
2
Order By: Relevance
“…Recently, Fusakio et al demonstrated that NKT cells are activated to produce IFN-γ and TNF-α during sepsis upon cognate engagement of C5a receptor (C5aR) in the presence of TLRs [29], suggesting cross-talk between C5a and IFN-γ-producing NKT cells during sepsis. C5a receptor-like 2 (C5L2) and C5aR have been reported to contribute synergistically to harmful effects on sepsis [15]. Moreover, C5L2 −/− mice show marginal improvement of survival in Escherichia coliinduced sepsis [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Fusakio et al demonstrated that NKT cells are activated to produce IFN-γ and TNF-α during sepsis upon cognate engagement of C5a receptor (C5aR) in the presence of TLRs [29], suggesting cross-talk between C5a and IFN-γ-producing NKT cells during sepsis. C5a receptor-like 2 (C5L2) and C5aR have been reported to contribute synergistically to harmful effects on sepsis [15]. Moreover, C5L2 −/− mice show marginal improvement of survival in Escherichia coliinduced sepsis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that complement protein C5a produces harmful effects in sepsis by inducing lymphocyte apoptosis and desensitizing neutrophils and monocytes, thereby suppressing immune responses [15,16]. C5a also induces multiple organ failure, cardiomyopathy, and imbalanced coagulation during sepsis [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C5L2, a putative ''default'' receptor, has been suggested to play important role in balancing the biological effect of C5a. For example, recent data showed that both C5aR and C5l2 cooperatively play functional parts in the setting of sepsis [5]. It has been shown that blockade of C5a or its receptor (C5aR) can inhibit the development of CLP and is associated with decreased levels of bacteria, preservation of innate immune functions of blood neutrophils, reduced thymocyte apoptosis and greatly improved survival rates [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Since C5a has the capacity to cause release of HMGB1 following stimulation of the second C5a receptor termed C5L2 generated on activated monocytes [11][12][13], inhibition of C5a successfully interferes with the above release which has the capacity to generate inflammatory cytokines stimulating TLR4 as an endogenous ligand ( Figure 2). …”
Section: Resultsmentioning
confidence: 99%